Baseline of Physiological Body Temperature and Hematological Parameters in Captive Rousettus aegyptiacus and Eidolon helvum Fruit Bats - Rissmann, Melanie; Friedrichs, Virginia; Kley, Nils; Straube, Martin; Sadeghi, Balal; Balkema-Buschmann, Anne (Frontiers in Physiology, 2022)
The discovery of bats as reservoir hosts for a number of highly pathogenic zoonotic agents has led to an increasing interest of infectious disease research in experimental studies with bats. Therefore, we established breeding colonies of Rousettus aegyptiacus and Eidolon helvum fruit bats, which both have been identified as reservoir hosts for relevant zoonotic disease agents, such as Marburg virus and Lagos bat virus. Since 2013, individuals of both species have been recruited to the Friedrich-Loeffler-Institut (FLI) from zoological gardens in Europe, to where these species had been introduced from the wild several decades ago. The aviaries have been designed according to national recommendations published by the Federal Ministry of Agriculture. Under these conditions, both species have been reproducing for years. To better understand the physiology of these animals, and to generate baseline knowledge for infection experiments, we monitored the body core temperatures of R. aegyptiacus bats in the aviaries, and found a circadian variation between 34°C and 41.5°C. We also determined the hematological parameters of both species, and detected specific differences between both bat species. For values of clinical chemistry, no correlation to age or sex was observed. However, species-specific differences were detected since ALT, BUN and CREA were found to be significantly higher in R. aegyptiacus and GLU and TP were significantly higher in E. helvum bats. A higher hematocrit, hemoglobin and red blood cell level was observed in subadult R. aegyptiacus, with hemoglobin and red blood cells also being significantly increased compared to E. helvum. Lymphocytes were found to be the dominant white blood cells in both species and are higher in female E. helvum. Neutrophil granulocytes were significantly higher in E. helvum bats. This underlines the necessity to define baseline profiles for each bat species prior to their use in experimental challenge.